Bergson's Intuition and Memory in View of NeuroQuantology - Güntekin, Bahar; BAŞAR, EROL (Anka Publısher, 116-11 Sok No.10 K 2 D 2, Bornova, Izmir 35050, Turkey, 2009)
This essay describes the concept of great philosopher Henri Bergson, related to episodic memory, intuition and duration. Further, the relation of "quantum theory" to Bergson's philosophy is shortly described. We discuss the importance of Bergson's concepts to "Quantum Methodology" and modern science.
Keywords: Bergson; quantum theory; quantum methodology; kuantum teorisi; kuantum metodoloji